REPRESENTING BALI’S WASTE CRISIS ON THE BRITISH BROADCASTING CORPORATION PODCAST: A SPEAKING MODEL AND TEXTUAL ANALYSIS - Ni Luh Sherin Prihantana; Ni Made Diana Erfiani; Yohanes Octovianus Lesu Awololon; Putu Chrisma Dewi (Universitas Duta Bangsa Surakarta, 2026)
Language is considered a vital instrument in shaping global public perception regarding environmental crises in the digital era. While communication studies are common, the exploration of global environmental issues in official news podcasts remains limited, particularly concerning the discrepancy between government rhetoric and international media representation. The objective of this study is to examine the representation of Bali’s waste crisis in the BBC podcast “Can Bali really go waste-free by 2027?”. A qualitative approach is employed, using the SPEAKING model to investigate the communication situation and Teun A. Van Dijk’s textual analysis to examine macrostructure, superstructure, and microstructure levels. Data are collected via non-participant observation and digital documentation. Through the SPEAKING model, it is evident that the BBC intentionally arranged the communication situation to contrast Bali’s iconic “paradise” image with systemic waste management failures, creating a serious and skeptical atmosphere. Furthermore, through textual analysis, the strategic use of critical lexicons such as “ambitious” and “pessimistic,” alongside powerful metaphors like “mountain of trash,” is identified to frame the crisis as a global emergency. These combined findings successfully demonstrate how a skeptical narrative is constructed toward government targets. It is concluded that the framing of environmental issues by international media significantly influences world perception in the digital era.